IMPLEMENTATION OF THE REGULATION OF THE HEAD OF THE NATIONAL DISASTER MANAGEMENT AGENCY NUMBER 9 OF 2008 CONCERNING RAPID RESPONSE TEAM PROCEDURES: Implementasi Peraturan Kepala Badan Nasional Penanggulangan Bencana Nomor 9 Tahun 2008 Tentang Prosedur Tim Reaksi Cepat - Sugiono; Harianto; Endang Murti (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the implementation of the Regulation of the Head of the National Disaster Management Agency Number 9 of 2008 concerning the Procedures of the Rapid Response Team (TRC) in Ngawi Regency in efforts to conduct disaster management in a rapid, accurate, and coordinated manner. This research applies the policy implementation theory perspectives of Donald Van Meter and Carl Van Horn, which emphasize six variables of successful policy implementation: policy standards and objectives, resources, characteristics of implementing agencies, attitudes or dispositions of implementers, inter-organizational communication, and social, economic, and political environments. The research method used is descriptive qualitative research, with data collected through interviews, observations, and documentation. The results show that the implementation of the Rapid Response Team procedures in Ngawi Regency has generally been carried out in accordance with existing regulations, particularly in the aspects of initial coordination and emergency response. However, the implementation process still faces several obstacles, including limited human resources with specialized disaster management competencies, inadequate supporting facilities and infrastructure, and logistical distribution challenges caused by geographical conditions and difficult terrain. In addition, inter-agency coordination is a crucial factor that greatly determines the effectiveness and success of disaster response efforts in Ngawi Regency.